2022
DOI: 10.1007/s11370-022-00438-2
|View full text |Cite
|
Sign up to set email alerts
|

Social robot advisors: effects of robot judgmental fallacies and context

Abstract: The role of social robots as advisors for decision making is investigated. We examined how robot advisors, one with logical reasoning and one with cognitive fallacies, affected participants' decision making under different contexts. The participants were asked to make multiple decisions, while advice from both robots interleaved the decision making process. Participants had to choose which robot they agreed with, and in the end of the scenario, rank the possible options presented to them. After the interaction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
(28 reference statements)
0
4
0
Order By: Relevance
“… 64 , 65 , 66 , 67 , 68 , 69 However, the extent to which an agent is perceived as “like-me” extends beyond physical form, capabilities, and movement, and growing evidence supports that prior knowledge about and the perceived socialness of a robot may more strongly influence their reception (and people’s ability to collaborate or cooperate with them in an intuitive manner) in social settings. 41 , 43 , 70 , 71 , 72 , 73 , 74 , 75 …”
Section: Discussionmentioning
confidence: 99%
“… 64 , 65 , 66 , 67 , 68 , 69 However, the extent to which an agent is perceived as “like-me” extends beyond physical form, capabilities, and movement, and growing evidence supports that prior knowledge about and the perceived socialness of a robot may more strongly influence their reception (and people’s ability to collaborate or cooperate with them in an intuitive manner) in social settings. 41 , 43 , 70 , 71 , 72 , 73 , 74 , 75 …”
Section: Discussionmentioning
confidence: 99%
“…[62][63][64][65][66][67] However, the extent to which an agent is perceived as "like-me" extends beyond physical form, capabilities, and movement, and growing evidence supports that prior knowledge about and the perceived socialness of a robot may more strongly influence their reception (and people's ability to collaborate or cooperate with them in an intuitive manner) in social settings. 41,44,[68][69][70][71][72][73] A few neuroimaging studies have investigated how these top-down knowledge cues and bottom-up stimulus cues influence perceptions of animacy and the flexibility of our social cognitive system. One study found that stimulus cues overrode knowledge cues to animacy 74 ; whereas, others found the inverse, knowledge, not stimulus, cues more strongly influenced animacy perception.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…These findings are conflicted and may be subject to unaddressed factors such as perceived animacy and embodiment. The information conveyed by the agent should not only consider the topic's sensitivity, but also be logical and free from fallacies (57), moral and attentive (58), all the while maintaining consistency with its physical or virtual representation (12; 30).…”
Section: Topic Sensitivitymentioning
confidence: 99%